Sensemaking the ‘social’ in social entrepreneurship - Kimmitt, Jonathan; Muñoz, Pablo (International small business journal, 2018)
In the collective imagination, the practices and outcomes of social entrepreneurship seem to hold hope for a better future. So far, these practices have been largely assumed as idealised types with the ‘social’ in social entrepreneurship underexplored. Such assumed neutrality, we argue, is hampering the development of a more robust theoretical corpus for understanding the phenomenon and inspiring practices that are more effective. In this article, we analyse the sensemaking of the social in social entrepreneurship by exploring the ways in which social entrepreneurs make sense of social problems and develop solutions for addressing them. Our empirical analyses of the stories of 15 social entrepreneurs indicate two distinct types of sensemaking and sensegiving practices, aligned with Amartya Sen’s notions of social justice. Drawing on these findings, sensemaking and social justice theory, we elaborate a two-type social sensemaking model pertaining to the appreciation and assessment of circumstances and the differing problem/solution combinations emerging from alternative ontological views of what constitutes a social problem.